Role of Convolvulus pluricaulis in Longevity through Mental Health Promotion: A Review - Gupta, Vinay Kumar; Sharma, Vinod (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a life science that aspires for the achievement of complete health. According to Acharya Charaka, the first aim of Ayurveda is to maintain health and the second is to cure diseases. Acharya Sushruta describes the definition of health and it is the most appropriate definition which includes all the aspects of quality of life. According to W.H.O. health is a state of complete physical, mental, spiritual and social well-being and not merely the absence of disease or infirmity. In Ayurveda, mental health is described as a balance of Manas Gunas like Satva, Raja, Tama and the use of medicinal plants has been mentioned for maintenance of physical and mental health for life longevity. Shankhapushpi (Convolvulus pluricaulis Choisy) is a prostrate, spreading, perennial, wild herb commonly found on sandy or rocky ground under xerophytic conditions in northern India having Tikta(Pungent), Katu(bitter) , Kashaya Rasa(astringent), Sara Guna, Sheeta Virya, Katu Vipaka and Smarti Vardhak, Medhya Rasayan properties. Many previous research works on Convolvulus pluricaulis have been reported its antiepileptic, brain tonic, nervine tonic, antioxidant, laxative, anti-ulcer effects. Thus, Convolvulus pluricaulis by their medicinal properties has been described in longevity through mental health promotion.